Dampak Sedentary Behavior terhadap Gangguan Psikososial dan Pertumbuhan Anak - Pitri Anggraeni; Suherman Slamet; Wildan Alfia Nugroho (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to analyze the impact of sedentary behavior, psychosocial disorders,and growth in elementary school children. This study used a quantitative approach with a non-parametric correlationaldesign. The study sample consisted of 49 fifth-grade students of SDN 024 Coblong, Bandung City, Selected using a total sampling technique. The result showed that sedentary behavior was in the high category, psychosocial disorders were in the abnormal, and growth was in the normal category. The results showed that sedentary behavior contributed 49,5% to psychosocial disorders and 5,3% to growth. Thus, it can be concluded that sedentary behavior has a more dominant influence on psychocosial disorders than growth. Keyword : Body Mass Index, Growth, Sedentary Behavior, Psychosocial Disorders